2013
DOI: 10.1007/s10773-013-1794-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Structures of a Model-Universe: An Inconsistency with Everett Interpretation of Quantum Mechanics

Abstract: We observe a Quantum Brownian Motion (QBM) Model Universe in conjunction with recently established Entanglement Relativity and Parallel Occurrence of Decoherence. The Parallel Occurrence of Decoherence establishes the simultaneous occurrence of decoherence for two mutually irreducible structures (decomposition into subsystems) of the total QBM model universe. First we find that Everett world branching for one structure excludes branching for the alternate structure and in order to reconcile this situation bran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This potential ambiguity is not peculiar to quantum mechanics: a theory of conscious observers in classical physics would also admit the logical possibility that a single physical structure could admit two different interpretations in terms of conscious beings. It is hard to imagine that this could actually occur with systems complex enough to record experiences; nevertheless, it has been shown that in simpler systems such ambiguous factorisation can arise in quantum mechanics, and that decoherence can be exhibited in both factorisations [11]. This does not show that an understanding based on such factorisation, like that outlined here, is untenable.…”
Section: The Futurementioning
confidence: 77%
“…This potential ambiguity is not peculiar to quantum mechanics: a theory of conscious observers in classical physics would also admit the logical possibility that a single physical structure could admit two different interpretations in terms of conscious beings. It is hard to imagine that this could actually occur with systems complex enough to record experiences; nevertheless, it has been shown that in simpler systems such ambiguous factorisation can arise in quantum mechanics, and that decoherence can be exhibited in both factorisations [11]. This does not show that an understanding based on such factorisation, like that outlined here, is untenable.…”
Section: The Futurementioning
confidence: 77%
“…( 5) cannot hold exactly. 8 This is a consequence of the Reeh-Schlieder theorem, 9 which similarly implies that no detector confined to a finite spatial region -as all physical detectors are -can ever record the presence of a particle-eigenstate with perfect accuracy [98]. This might be a signal that the concept of spatially disjoint records will eventually need to be generalized in the relativistic domain, or simply that branches will only ever be well-defined asymptotically (as are particle in-states and out-states).…”
Section: B Branching Of Fieldsmentioning
confidence: 86%
“…This is indeed a significant reduction, as the number of bases is much larger than the number of subsystems, and the subsystems that are feasibly accessible to experiment are much more salient than the bases. Although this is sufficient for most practical purposes, the formal problem of identifying the preferred subsystems 1 from first principles remains [7][8][9].…”
mentioning
confidence: 99%
“…While quantum structural studies challenge [26] the interpretations á la Everett [25,27], the discourses regarding the non-universally valid quantum theory [28] as well as "the problem of time" [29][30][31] (and references therein) are in order. To this end, the work is in progress and the results will be presented elsewhere.…”
Section: Discussionmentioning
confidence: 99%